Investigating the bioavailability of graphene quantum dots in lung tissues via Fourier transform infrared spectroscopy. Issue 3 (20th April 2018) - Tabish, Tanveer A.; Lin, Liangxu; Ali, Muhammad; Jabeen, Farhat; Ali, Muhammad; Iqbal, Rehana; Horsell, David W.; Winyard, Paul G.; Zhang, Shaowei
Abstract : Biomolecular fractions affect the fate and behaviour of quantum dots (QDs) in living systems but how the interactions between biomolecules and QDs affect the bioavailability of QDs is a major knowledge gap in risk assessment analysis. The transport of QDs after release into a living organism is a complex process. The majority accumulate in the lungs where they can directly affect the inhalation process and lung architecture. Here, we investigate the bioavailability of graphene quantum dots (GQDs) to the lungs of rats by measuring the alterations in macromolecular fractions via Fourier transform infrared spectroscopy (FTIR). GQDs were intravenously injected into the rats in a dose-dependent manner (low (5 mg kg −1 ) and high (15 mg kg −1 ) doses of GQDs per body weight of rat) for 7 days. The lung tissues were isolated, processed and haematoxylin–eosin stained for histological analysis to identify cell death. Key biochemical differences were identified by spectral signatures: pronounced changes in cholesterol were found in two cases of low and high doses; a change in phosphorylation profile of substrate proteins in the tissues was observed in low dose at 24 h. This is the first time biomolecules have been measured in biological tissue using FTIR to investigate the biocompatibility of foreign material. We found that highly accurate toxicological changes can be investigated with FTIR measurements of tissue sections. As a result, FTIR could form the basis of a non-invasive pre-diagnostic tool for predicting the toxicity of GQDs.